Die vergessene vierte Säule: Die Gründung von Staats und Landesbanken in der deutschen Kreditwirtschaft - Harald Wixforth (IBF - Institut für Bank- und Finanzgeschichte e.V., 2023)
– The German financial system rests on three distinct pillars - this position has been widely accepted among bank historians. However, this view neglects another important pillar, namely the financial institutions under the rule and control of state authorities. The following article aims to describe the history and development of the state-owned banks and the large federal banks in the hands of public institutions in order to encourage further research on the history of the forgotten "fourth pillar" up to the present times.
Keywords: N23; N24; G21; 330; banks under governmental rule and control; credit economy; banking system Germany; economic constitution; Reichs-Kredit-Gesellschaft